HOME PURCHASE AND SALE AGREEMENT BEFORE A NOTARY FOLLOWED BY AN ACKNOWLEDGMENT OF DEBT - Abu, Achmad Nur; Subekti, Subekti; Djaja, Dudik (EQUALEGUM International Law Journal, 2024)
Background. A notary is a public official authorized to make deeds regarding actions, agreements, and decisions required by general legislation, or to express the wishes of parties involved. This research aims (a) to determine and analyze the authority of notaries in making PPJB for houses followed by debt recognition. (b) to analyze the validity of the PPBJ made by a notary for the purposes of debt recognition. Research Method. The type of research used is normative juridical, using a statutory approach. This research uses three types of legal materials, namely primary legal materials, secondary legal materials and tertiary legal materials. The process of analyzing legal materials in this research uses the interpretation method. Findings. The results of the research show that (a) The notary executes the original deed, considering all required deeds, agreements, and provisions. They have the right to keep a certificate. If contested, the Department of Security has a regulatory role regarding the sale and purchase contract. (b) PPJB is a debt recognition form made in an authentic deed, which should be disclosed to the public for completeness. However, the deed's validity may be canceled due to legal cover-up, potentially resulting in a default case, depending on the judge's decision. Conclusion. Notaries must act honestly and impartially to make authentic deeds, providing counseling before executing the Sales and Purchase Agreement (PPJB) for debt recognition purposes, as the deed's validity may be canceled if it doesn't comply with the law.